Anthelmintic Potency of Garlic (Allium sativum) and Neem (Azadirachta indica) combination As Herbal Anthelmintic in Lactating Karan Fries Cows - Adhana, Mamta; Lathwal, S S; Singh, Pawan; Devi, Indu; Kumar, Ajay (The Indian Journal of Animal Sciences, 2022)
Gastro-intestinal parasites affect the health and production performance of dairy cows under tropical and sub-tropical conditions. This study was conducted to evaluate the anthelmintic efficacy of herbal anthelmintic (Neem and Garlic combination) as an effective alternative for chemical dewormers which has chemical toxicity and resistance problems in dairy cows. For this, EPG count for gastrointestinal parasites, body weight and BCS of cows were studied. Freshly calved crossbred KF (n=28) cows were selected and divided into 4 groups (T1, T2, T3, T4), each having 7 cows. The cows of T1 were used as control; in T2, cows were provided the commercial (synthetic) dewormer; in T3 cows were provided with a dose of combination of garlic and neem in the ratio of 1:5 @ 4g/kg body wt. at 7 days after parturition and in T4, in addition to first dose at 7 days, a second dose was also supplemented at day 60. Sampling for fecal sample was done on 0, 1, 2, 3, 4, 5, 6, 7, 8 fortnights relative to the deworming treatment. The EPG counting was done by using McMaster counting chamber. The average fecal egg count (FCE) reduction was significantly (P<0.05) maximum in T2 (83.20%) group followed by T4 (77.48%). The BCS and FCE were found significantly (P<0.05) better in all the anthelmintic treated groups compared to control group. However, the FCE was significantly (P<0.05) better in herbal treated groups (T3 and T4) compared to the synthetic anthelmintic treated group (T2). Based on the findings, it could be concluded that Garlic and Neem combination is effective herbal dewormer/anthelmintic and might be used against nematodes in dairy cattle as an effective alternative of synthetic anthelmintics drugs. Â